Biomimetic wall-shaped adhesive microstructure for shear-induced attachment: the effects of pulling angle and preliminary displacement. Issue 137 (13th December 2017) - Kim, Jae-Kang; Varenberg, Michael
Abstract : To date, a handful of different gecko-like adhesives inspired by spatula-shaped attachment hairs have been suggested based on wedge and flap geometry of contact elements. However, while these surface designs have been shown to have directionality in adhesion, high friction, long lifetime and the ability to work in vacuum, an experimental verification of the very basic concept of the pulling angle effect has not yet been reported. To close this gap, here we use wall-shaped adhesive microstructures of three different flap heights to systematically study the effect of pulling angle on the normal and tangential components of the pull-off force tested at different preliminary tangential displacements. In accord with the prediction of the Kendall model for the normal component of peeling force, there is an optimal normal force that is required to detach the wall-shaped adhesive microstructure. The optimum is obtained at about half the distance needed to initiate sliding and at pulling angles that range within 60–90°, which suggests that the wall-shaped microstructure can tolerate relatively large inaccuracies in the loading direction. The increase of the attachment force with increasing flap height is found to correlate with the flap thickness, which decreased with increasing flap height.